Method for manufacturing a polymer having compatibility with biomaterials

KR103013715B1Active Publication Date: 2026-09-02NISSAN CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
KR1020217026639
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-12
Filing Date
2020-02-12
Publication Date
2026-09-02
Estimated Expiration
2040-02-12

Smart Images

  • Figure 112021096442417-PCT00026_ABST
    Figure 112021096442417-PCT00026_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a copolymer-containing varnish that does not exhibit gelation problems by using a monomer having specific unsaturated bonds, a method for manufacturing a composition, a method for manufacturing a coating film, preferably a method for manufacturing a coating film having compatibility with biomaterials (having the ability to inhibit biomaterial adhesion or promote cell culture). Formulas (1) and (2) below: A method for manufacturing a copolymer-containing varnish comprising a process of copolymerizing a monomer mixture containing a compound represented by (in Formula (1), R1 represents a hydrogen atom or a methyl group, R2 represents an alkylene group having 1 to 6 carbon atoms, and n represents an integer from 1 to 30, and in Formula (2), R11 represents a hydrogen atom or a methyl group, and A1 represents a monovalent organic group having cationicity) in a polymerization solvent in the presence of a radical polymerization initiator, wherein the mass% of the compound represented by Formula (1) among the phosphorus-containing compounds contained in the monomer mixture is 70 mass% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing a copolymer-containing varnish that does not cause gelation problems, a method for manufacturing a composition for forming a coating film, a method for manufacturing a coating film, and preferably a method for manufacturing a coating film having compatibility with biomaterials (e.g., having the ability to inhibit biomaterial adhesion or promote cell culture). Background Technology

[0002] Coating materials having the ability to inhibit the adhesion of various biomaterials, or coating materials for promoting cell culture, have been proposed to inhibit the adhesion of biomaterials to medical devices and materials such as artificial dialysis machines, artificial organs, and medical instruments.

[0003] Patent Document 1 discloses an ion complex material having the ability to control the attachment of biomaterials and a method for manufacturing the same. Patent Document 2 discloses a surface treatment agent having excellent properties such as antifouling properties. Prior art literature

[0004] International Release No. 2014 / 196650 International Release No. 2018 / 008663 The problem to be solved

[0005] Phosphate ester monomers having unsaturated bonds contain a large amount of impurities, such as phosphate diesters, according to conventional synthesis methods. When a phosphate ester monomer having unsaturated bonds containing a large amount of phosphate diesters is used in a copolymerization reaction with other monomers having different unsaturated bonds, a three-dimensional network structure is formed in which the phosphate diesters become crosslinking elements, and gelation occurs, which has a problem in that the polymer cannot be dissolved or dispersed in a solvent to form a varnish.

[0006] As a result of careful examination by the inventors of the present invention, it was discovered that a copolymer-containing varnish can be produced without gelling by copolymerizing a phosphate ester monomer having a specific structural formula of a certain purity or higher with a monomer having different unsaturated bonds using a method known in itself.

[0007] The present invention provides a method for manufacturing a copolymer-containing varnish that does not cause gelation problems, a method for manufacturing a composition, a method for manufacturing a coating film, and preferably a method for manufacturing a coating film having suitability for biomaterials (e.g., having the ability to inhibit biomaterial adhesion or promote cell culture). means of solving the problem

[0008] The present invention includes the following.

[0009] [1]

[0010] The following equations (1) and (2):

[0011] [Chemical Formula 1]

[0012]

[0013] [Chemical Formula 2]

[0014]

[0015] (In Equation (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group having 1 to 6 carbon atoms, and n represents an integer from 1 to 30, and in Equation (2), R 11 represents a hydrogen atom or a methyl group, and A 1 A method for manufacturing a copolymer-containing varnish comprising a process of copolymerizing a monomer mixture containing a compound represented by (which represents a monovalent organic group having cationic properties) in a polymerization solvent in the presence of a radical polymerization initiator,

[0016] A method of manufacturing in which the mass% of the compound represented by Formula (1) among the phosphorus-containing compounds included in the monomer mixture is 70 mass% or more.

[0017] [2]

[0018] Above A 1 This, the following formula (2-1):

[0019] [Chemical Formula 3]

[0020]

[0021] (U b1 , U b2 and U b3 Each independently represents a hydrogen atom or a straight-chain or branched alkyl group having 1 to 5 carbon atoms, and An - A method for preparing a copolymer-containing varnish described in [1], comprising a structure represented by an anion selected from the group consisting of halide ions, inorganic acid ions, hydroxide ions and isothiocyanate ions.

[0022] [3]

[0023] Above A 1 This, the following formula (2-2):

[0024] [Chemical Formula 4]

[0025]

[0026] (R 21 ...represents an alkylene group having 1 to 6 carbon atoms that may be interrupted by a phosphate diester bond, and U b1 , U b2 and U b3 Each independently represents a hydrogen atom or a straight-chain or branched alkyl group having 1 to 5 carbon atoms, and An - A method for preparing a copolymer-containing varnish as described in [1], represented by an anion selected from the group consisting of halide ions, inorganic acid ions, hydroxide ions and isothiocyanate ions.

[0027] [4]

[0028] The following equations (1) and (2):

[0029] [Chemical Formula 5]

[0030]

[0031] [Chemical Formula 6]

[0032]

[0033] (In Equation (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group having 1 to 6 carbon atoms, n represents an integer from 1 to 30, and in Equation (2), R 11 represents a hydrogen atom or a methyl group, and A 1 A method for preparing a coating film-forming composition comprising: a process of copolymerizing a monomer mixture containing a compound represented by (which represents a monovalent organic group having cationicity) in a polymerization solvent in the presence of a radical polymerization initiator, and then a process of adding a solvent.

[0034] A method of manufacturing in which the mass% of the compound represented by Formula (1) among the phosphorus-containing compounds included in the monomer mixture is 70 mass% or more.

[0035] [5]

[0036] A method for preparing a coating film-forming composition described in [4], having suitability for biomaterials.

[0037] [6]

[0038] A method for manufacturing a coating film comprising the process of applying a coating film-forming composition described in [4] or [5] to a substrate. Effects of the invention

[0039] According to the method of the present invention, a method for manufacturing a copolymer-containing varnish that does not cause gelation problems, a method for manufacturing a composition for forming a coating film, a method for manufacturing a coating film, and preferably a method for manufacturing a coating film having suitability for biomaterials (e.g., having the ability to inhibit biomaterial adhesion or promote cell culture). Brief explanation of the drawing

[0040] Figure 1 is a micrograph showing the cell adhesion inhibitory effect of a well coated with the coating film forming composition of Example 1 in Test Example 1. Figure 2 is a micrograph showing the cell adhesion inhibitory effect of a well coated with the coating film forming composition of Example 2 in Test Example 1. Figure 3 is a micrograph showing the cell adhesion inhibitory effect of a well coated with the coating film forming composition of Example 3 in Test Example 1. Figure 4 is a micrograph showing the cell adhesion inhibitory effect of a well coated with the coating film forming composition of the positive control (Reference Example 1) in Test Example 1. Figure 5 is a micrograph showing the cell adhesion inhibitory effect of the negative control (uncoated) well in Test Example 1. Specific details for implementing the invention

[0041] ≪Glossary≫

[0042] The terms used in the present invention have the following definitions unless otherwise specifically stated.

[0043] "Alkylene groups having 1 to 6 carbon atoms" refers to methylene group, ethylene group, n-propylene (trimethylene) group, propylene group, cyclopropylene group, n-butylene group, isobutylene group, s-butylene group, t-butylene group, cyclobutylene group, 1-methyl-cyclopropylene group, 2-methyl-cyclopropylene group, n-pentylene group, 1-methyl-n-butylene group, 2-methyl-n-butylene group, 3-methyl-n-butylene group, 1,1-dimethyl-n-propylene group, 1,2-dimethyl-n-propylene group, 2,2-dimethyl-n-propylene group, 1-ethyl-n-propylene group, cyclopentylene group, 1-methyl-cyclobutylene group, 2-methyl-cyclobutylene group, 3-methyl-cyclobutylene group, 1,2-dimethyl-cyclopropylene group, 2,3-dimethyl-cyclopropylene group, 1-ethyl-cyclopropylene group, 2-ethyl-cyclopropylene group, n-hexylene group, 1-methyl-n-pentylene group, 2-methyl-n-pentylene group, 3-methyl-n-pentylene group, 4-methyl-n-pentylene group, 1,1-dimethyl-n-butylene group, 1,2-dimethyl-n-butylene group, 1,3-dimethyl-n-butylene group, 2,2-dimethyl-n-butylene group, 2,3-dimethyl-n-butylene group, 3,3-dimethyl-n-butylene group, 1-ethyl-n-butylene group, 2-ethyl-n-butylene group, 1,1,2-trimethyl-n-propylene group, 1,2,2-trimethyl-n-propylene group, 1-ethyl-1-methyl-n-propylene group, 1-ethyl-2-methyl-n-propylene group, cyclohexylene group, 1-methyl-cyclopentylene group, 2-methyl-cyclopentylene group, 3-methyl-cyclopentylene group, 1-ethyl-cyclobutylene group, 2-ethyl-cyclobutylene group, 3-ethyl-cyclobutylene group, 1,2-dimethyl-cyclobutylene group, 1,3-dimethyl-cyclobutylene group, 2,2-dimethyl-cyclobutylene group, 2,3-dimethyl-cyclobutylene group, 2,4-dimethyl-cyclobutylene group, 3,3-dimethyl-cyclobutylene group, 1-n-propyl-cyclopropylene group, 2-n-propyl-cyclopropylene group, 1-isopropyl-cyclopropylene group, 2-isopropyl-cyclopropylene group, 1,2,2-trimethyl-cyclopropylene group, 1,2,3-trimethyl-cyclopropylene group, 2,2,3-trimethyl-cyclopropylene group, 1-ethyl-2-methyl-cyclopropylene group, 2-ethyl-1-methyl-cyclopropylene group,Examples include 2-ethyl-2-methyl-cyclopropylene groups and 2-ethyl-3-methyl-cyclopropylene groups.

[0044] Also, “an alkylene group having 1 to 6 carbon atoms that may be interrupted by a phosphate diester bond” means “an alkylene group having 1 to 6 carbon atoms” or “an alkylene group having 1 to 6 carbon atoms that is interrupted by a phosphate diester bond”.

[0045] Examples of “alkylene groups having 1 to 6 carbon atoms” are as above. “Alkylene groups having 1 to 6 carbon atoms interrupted by phosphodiester bonds” means a divalent group in which at least one methylene (-CH2-) group of the “alkylene groups having 1 to 6 carbon atoms” is substituted by a phosphodiester bond.

[0046] Examples of “straight-chain or branched alkyl groups having 1 to 5 carbon atoms” include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, s-butyl group, t-butyl group, n-pentyl group, 1-methylbutyl group, 2-methylbutyl group, 3-methylbutyl group, 1,1-dimethylpropyl group, 1,2-dimethylpropyl group, 2,2-dimethylpropyl group, or 1-ethylpropyl group.

[0047] Examples of "halogen ions" include fluoride ions, chloride ions, bromide ions, or iodide ions.

[0048] Examples of “inorganic acid ions” include carbonate ions, sulfate ions, phosphate ions, hydrogen phosphate ions, dihydrogen phosphate ions, nitrate ions, perchlorate ions, or borate ions.

[0049] "Polymerization solvent" refers to a solvent used in a self-known copolymerization reaction of two or more monomers of the present invention, and may be water, phosphate buffer, an alcohol such as ethanol, or a mixed solvent combining these, but it is preferable to include water or ethanol. Furthermore, it is preferable to include water or ethanol in an amount of 10 mass% or more and 100 mass% or less. Furthermore, it is preferable to include water or ethanol in an amount of 50 mass% or more and 100 mass% or less. Furthermore, it is preferable to include water or ethanol in an amount of 80 mass% or more and 100 mass% or less. Furthermore, it is preferable to include water or ethanol in an amount of 90 mass% or more and 100 mass% or less. Preferably, the total amount of water and ethanol is 100 mass%.

[0050] "Radical polymerization initiator" may be a "thermal radical polymerization initiator" or a "photoradical polymerization initiator."

[0051] As "thermal radical polymerization initiators," 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile) (Fujifilm Wako Pure Chemicals Co., Ltd. Product name: V-65, 10-hour half-life, temperature: 51°C), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, 2,2'-azobis[2-(2-imidazoline-2-yl)propane] 2 hydrochloride (Fujifilm Wako Pure Chemicals) (Inc. ; VA-044, 10-hour half-life temperature ; 44 ℃), 2,2'-Azobis[2-(2-imidazoline-2-yl)propane] (Fujifilm Wako Pure Pharmaceuticals Inc. ; VA-061, 10-hour half-life temperature ; 61 ℃), 2,2'-Azobis(2-methylpropionamidine) 2-hydrochloride, 2,2'-Azo(2-methyl-N-(2-hydroxyethyl)propionamide (Fujifilm Wako Pure Pharmaceuticals Inc. Product Name ; VA-086, 10-hour half-life temperature ; 86 ℃), benzoyl peroxide (BPO), 2,2'-Azobis(N-(2-carboxyethyl)-2-methylpropionamidine) n-hydrate (Fujifilm Wako Pure Pharmaceuticals Inc. Product Name ; VA-057, 10-hour half-life temperature; 57 ℃), 4,4'-Azobis(4-cyanopentanoic acid) (Fujifilm Wakou Pure Pharmaceuticals Co., Ltd. Product name; VA-501), 2,2'-Azobis[2-(2-imidazoline-2-yl)propane]disulfite dihydrate (Fujifilm Wakou Pure Pharmaceuticals Co., Ltd. Product name; VA-046B, 10-hour half-life temperature; 46 ℃), 2,2'-Azobis(2-amidinopropane)dihydrochloride (Fujifilm Wakou Pure Pharmaceuticals Co., Ltd. Product name; V-50, 10-hour half-life temperature; 56 ℃), peroxo disulfide or t-butylhydroperoxide, dimethyl 1,1'-Azobis(1-cyclohexanecarboxylate) (Fujifilm Wakou Pure Medicine Co., Ltd. Product Name; VE-073) etc. are used.

[0052] As "photoradical polymerization initiators," acetophenone, chloroacetophenone, hydroxyacetophenone, 2-aminoacetophenone, dialkylaminoacetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2'-phenylacetophenone (BASF product name: Irgacure 651), 2-hydroxy-2-methyl1-phenylpropanone (BASF product name: Irgacure 1173), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxymethylpropanone (BASF product name: Irgacure 2959), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methyl-1-propan-1-one (BASF product name: Irgacure 127), Acetophenones such as 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (BASF product name; Irgacure 907) and 2-benzyl-2-(dimethylamino)-4-morpholinobutyrophenone (BASF product name; Irgacure 369); benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 1-hydroxycyclohexylphenyl ketone (BASF product name; Irgacure 184); Benzophenones such as benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, methyl-o-benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, hydroxypropylbenzophenone, acrylbenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-dichlorobenzophenone, etc.; thioxantones such as thioxantone, 2-chlorothioxantone, 2-methylthioxantone, diethylthioxantone, dimethylthioxantone, etc.; acylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (BASF product name: IrgacureTPO) and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (BASF product name: Irgacure819); A mixture of oxyphenylacetic acid, 2-[2-oxo-2-phenylacetoxyethoxy]ethyl ester and oxyphenylacetic acid, 2-(2-hydroxyethoxy)ethyl ester (BASF product name ;Examples include Irgacure 754), methyl benzoyl formate (BASF product name; IrgacureMBF), α-acyloxime esters, benzyl-(o-ethoxycarbonyl)-α-monooxime, glyoxyesters, 2-ethylanthraquinone, campaquinone, tetramethylthiuram sulfide, azobis-isobutyronitrile, benzoyl peroxide, dialkyl peroxide, tert-butylperoxypivalate, etc.;

[0053] "Solvent" refers to a solvent used in the composition for forming a coating film of the present invention, and examples include water, phosphate-buffered physiological saline (PBS), and alcohol. As alcohols, alcohols having 2 to 6 carbon atoms, for example, ethanol, propanol, isopropanol, 1-butanol, 2-butanol, isobutanol, t-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 1-heptanol, 2-heptanol, 2,2-dimethyl-1-propanol (=neopentyl alcohol), 2-methyl-1-propanol, 2-methyl-1-butanol, 2-methyl-2-butanol (=t-amyl alcohol), 3-methyl-1-butanol, 3-methyl-3-pentanol, cyclopentanol, 1-hexanol, 2-hexanol, 3-hexanol, 2,3-dimethyl-2-butanol, 3,3-dimethyl-1-butanol, Examples include 3,3-dimethyl-2-butanol, 2-ethyl-1-butanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-methyl-3-pentanol, 3-methyl-1-pentanol, 3-methyl-2-pentanol, 3-methyl-3-pentanol, 4-methyl-1-pentanol, 4-methyl-2-pentanol, 4-methyl-3-pentanol, and cyclohexanol. A solvent may be used alone or in combination thereof, but for the sake of solubility of the copolymer, it is preferable to select from water, PBS, ethanol, and propanol.

[0054] "Biomaterials" include proteins, sugars, nucleic acids, cells, or combinations thereof. For example, proteins include fibrinogen, bovine serum albumin (BSA), human albumin, various globulins, β-lipoprotein, various antibodies (IgG, IgA, IgM), peroxidase, various complements, various lectins, fibronectin, lysozyme, von Willebrand factor (vWF), serum γ-globulin, pepsin, egg white albumin, insulin, histones, ribonucleases, collagen, cytochrome c; for example, sugars include glucose, galactose, mannose, fructose, heparin, hyaluronic acid; for example, nucleic acids include deoxyribonucleic acid (DNA) and ribonucleic acid (RNA); for example, cells include afibroblasts, bone marrow cells, B lymphocytes, T lymphocytes, neutrophils, erythrocytes, platelets, macrophages, monocytes, osteocytes, peritrate cells, dendritic cells, keratinocytes, adipocytes, mesenchymal cells, Epithelial cells, epidermal cells, endothelial cells, vascular endothelial cells, hepatic parenchymal cells, chondrocytes, cumulus cells, nervous system cells, glial cells, neurons, oligodendrocytes, microglia, astrocytes, cardiac cells, esophageal cells, muscle cells (e.g., smooth muscle cells or skeletal muscle cells), pancreatic beta cells, melanocytes, hematopoietic progenitor cells, monocytes, embryonic stem cells (ES cells), embryonic tumor cells, embryonic germ cells, induced pluripotent stem cells (iPS cells), neural stem cells, hematopoietic stem cells, mesenchymal stem cells, liver stem cells, pancreatic stem cells, myostem cells, germ cells, intestinal stem cells, cancer stem cells, follicular stem cells, and various cell lines (e.g., HCT116, Huh7, HEK293 (human fetal renal cells), HeLa (human cervical cancer cell line), HepG2 (human liver cancer cell line), UT7 / TPO (human leukemia cell line), CHO (Chinese hamster ovary) Examples include cell lines), MDCK, MDBK, BHK, C-33A, HT-29, AE-1, 3D9, Ns0 / 1, Jurkat, NIH3T3, PC12, S2, Sf9, Sf21, High Five, Vero, etc.

[0055] "Having the ability to inhibit the attachment of biomaterials" means, for example,

[0056] In the case where the biomaterial is platelets, it means that in a platelet adhesion test performed by the method described in the example of republished patent 2016 / 093293, the relative number of platelets attached (%) when compared to the absence of a coating film ((number of platelets attached in the example (pieces)) / (number of platelets attached in the comparative example (pieces))) is 50% or less, preferably 30% or less, and more preferably 20% or less;

[0057] In the case where the biomaterial is a protein, it means that in the QCM-D measurement performed by the method described in the example, the relative mass per unit area (%) ((mass per unit area of ​​the example (ng / cm²) / (mass per unit area of ​​the comparative example (ng / cm²))) when compared to the absence of a coating film is 50% or less, preferably 30% or less, and more preferably 20% or less;

[0058] In the case where the biomaterial is a cell, the relative absorbance (WST OD 450 nm) (%) when compared to the absence of a coating film by fluorescence microscopy performed by the method described in the example of republished patent 2016 / 093293 ((absorbance of the example (WST OD 450 nm))) / (absorbance of the comparative example (WST OD 450 nm))) means that it is 50% or less, preferably 30% or less, and more preferably 20% or less.

[0059] Method for manufacturing copolymer-containing varnish

[0060] The present invention is based on the following formulas (1) and (2):

[0061] [Chemical Formula 7]

[0062]

[0063] [Chemical Formula 8]

[0064]

[0065] (In Equation (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group having 1 to 6 carbon atoms, n represents an integer from 1 to 30, and in Equation (2), R 11 represents a hydrogen atom or a methyl group, and A 1 A method for manufacturing a copolymer-containing varnish comprising a process of copolymerizing a monomer mixture containing a compound represented by (which represents a monovalent organic group having cationic properties) in a polymerization solvent in the presence of a radical polymerization initiator,

[0066] This is a manufacturing method in which the mass % (purity) of the compound represented by Formula (1) among the phosphorus-containing compounds included in the above monomer mixture is 70 mass % or more.

[0067] In the present invention, "monomer mixture" refers to a mixture comprising all compounds provided to the copolymerization reaction process, in addition to all compounds represented by Formula (1) and Formula (2). That is, "mass % (absolute mass %) of the compound represented by Formula (1) among the phosphorus-containing compounds included in the monomer mixture" may be rephrased as having a purity (content) of the compound represented by Formula (1) of 70 mass % or more relative to the total amount of phosphorus-containing compounds included in the monomer mixture provided to the copolymerization reaction process.

[0068] The above phosphorus-containing compound refers to a compound containing at least one phosphorus atom in one molecule of the compound, and in addition to the compound represented by Formula (1), it is an impurity derived from the compound represented by Formula (1) (e.g., a phosphate diester compound equivalent to a dimer of the compound represented by Formula (1)).

[0069] n represents an integer from 1 to 30, but it is preferable that it be an integer from 1 to 20, an integer from 1 to 10, an integer from 1 to 7, an integer from 2 to 6, or an integer from 3 to 5.

[0070] The compound represented by formula (1) may use the monomer described in Japanese Patent Publication No. 2018-27927.

[0071] The mass % (absolute mass %) of the compound represented by Formula (1) among the phosphorus-containing compounds included in the monomer mixture used to manufacture the copolymer above can be obtained, for example, by compositional analysis of the phosphorus-containing compounds described in the examples.

[0072] It is preferable that the mass% (absolute mass%) of the phosphorus-containing compound represented by Formula (1) is 70 mass% or more, 75 mass% or more, 80 mass% or more, 85 mass% or more, 90 mass% or more, or 95 mass% or more. Most preferably, it is 100 mass%.

[0073] The ratio of repeating units derived from the compound represented by formula (1) in the copolymer related to the present invention is R of the compound represented by formula (2) described later. 21 In the case of an alkylene group having 1 to 6 carbon atoms interrupted by a phosphate diester bond, the amount is 5 mol% to 80 mol%, preferably 7 mol% to 70 mol%, preferably 8 mol% to 65 mol%, and more preferably 10 mol% to 60 mol%.

[0074] The ratio of repeating units derived from the compound represented by formula (1) in the copolymer related to the present invention is R of the compound represented by formula (2) described later. 21 This is not interrupted by the phosphodiester bond (i.e., R 21 In the case where it is an alkylene group having 1 to 6 carbon atoms, it is 10 mol% to 80 mol%, preferably 30 mol% to 70 mol%, and more preferably 40 mol% to 60 mol%.

[0075] In addition, the copolymer related to the present invention may include repeating units derived from two or more compounds represented by formula (1), but preferably one or two, and preferably one.

[0076] The ratio of repeating units derived from the compound represented by Formula (2) in the copolymer related to the present invention may be the entire remainder after subtracting Formula (1) from the total copolymer, or the remainder after subtracting the ratio of the sum of Formula (1) and the third component described below. Additionally, the copolymer related to the present invention may include repeating units derived from two or more compounds represented by Formula (2).

[0077] The monomer mixture related to the present invention may additionally include, as an optional third component, an ethylenically unsaturated monomer, or a polysaccharide or a derivative thereof. Examples of ethylenically unsaturated monomers include one or more ethylenically unsaturated monomers selected from the group consisting of (meth)acrylic acid and its esters; vinyl acetate; vinylpyrrolidone; ethylene; vinyl alcohol; and their hydrophilic functional derivatives. Examples of polysaccharides or their derivatives include cellulose-based polymers such as hydroxyalkylcellulose (e.g., hydroxyethylcellulose or hydroxypropylcellulose), starch, dextran, and curdran.

[0078] A hydrophilic functional derivative refers to an ethylenically unsaturated monomer having a hydrophilic functional group or structure. Examples of hydrophilic functional groups or structures include amide structures; alkylene glycol residues; amino groups; and sulfinyl groups.

[0079] The amide structure is the following formula:

[0080] [Chemical Formula 9]

[0081]

[0082] [Here, R 16 , R 17 and R 18 [It is, independently of each other, a hydrogen atom or an organic group (e.g., a methyl group, a hydroxymethyl group, or a hydroxyethyl group, etc.)]

[0083] It refers to a group represented by. Examples of ethylenically unsaturated monomers having such a structure include (meth)acrylamide, N-(hydroxymethyl)(meth)acrylamide, etc. Additionally, monomers or polymers having such a structure are disclosed, for example, in Japanese Patent Publication No. 2010-169604.

[0084] An alkylene glycol residue refers to an alkyleneoxy group (-Alk-O-) remaining after the hydroxyl groups of one or both ends of an alkylene glycol (HO-Alk-OH; where Alk is an alkylene group having 1 to 10 carbon atoms) undergo a condensation reaction with another compound, and also includes a poly(alkyleneoxy) group in which alkyleneoxy units are repeated. Examples of ethylenically unsaturated monomers having such a structure include 2-hydroxyethyl (meth)acrylate and methoxypolyethylene glycol (meth)acrylate. Furthermore, monomers or polymers having such a structure are disclosed, for example, in Japanese Patent Publication No. 2008-533489.

[0085] The amino group is formula: -NH2, -NHR 19 or -NR 20 R 21 [Here, R 19 , R 20 and R 21[It refers to a group represented as] which is an organic group (e.g., a straight-chain or branched alkyl group having 1 to 5 carbon atoms, etc.) independently of each other. The amino group in the present invention includes a quaternized or chlorinated amino group. Examples of ethylenically unsaturated monomers having such a structure include dimethylaminoethyl (meth)acrylate, 2-(t-butylamino)ethyl (meth)acrylate, methacryloylcholine chloride, etc.

[0086] The sulfinyl group is in the following formula:

[0087] [Chemical Formula 10]

[0088]

[0089] [Here, R 22 is an organic group (e.g., an organic group having 1 to 10 carbon atoms, preferably an alkyl group having 1 to 10 carbon atoms having one or more hydroxyl groups, etc.)

[0090] It means a group represented by. Examples of polymers having such a structure include copolymers disclosed in Japanese Patent Publication No. 2014-48278, etc.

[0091] (Weight-average molecular weight of the copolymer)

[0092] The weight molecular weight of the copolymer related to the present invention may be in the range of thousands to millions, preferably 5,000 to 5,000,000. More preferably, it is 10,000 to 2,000,000. In addition, it may be any of a random copolymer, a block copolymer, or a graft copolymer, and there are no particular restrictions on the copolymerization reaction itself for producing the copolymer; methods of synthesis in a known solution, such as radical polymerization, ionic polymerization, photopolymerization, macromers, or emulsion polymerization, may be used. Depending on the intended use, any of the copolymers of the present invention may be used alone, a plurality of copolymers may be mixed, or their ratios may be changed.

[0093] (Copolymerization reaction)

[0094] The copolymer-containing varnish of the present invention can be manufactured by a manufacturing method comprising a process of reacting (polymerizing) a monomer mixture containing compounds represented by formulas (1) and (2) in a polymerization solvent at a total concentration of 0.01 mass% to 20 mass% of both compounds.

[0095] The amount of radical polymerization initiator added is 0.05 mass% to 10 mass% with respect to the total weight of the monomer used in polymerization.

[0096] The reaction conditions are such that the reaction vessel is heated to 50°C to 200°C using an oil bath or the like, and stirring is performed for 1 to 48 hours, more preferably at 80°C to 150°C, for 5 to 30 hours, thereby carrying out the polymerization reaction to obtain the copolymer of the present invention. The reaction atmosphere may be an atmospheric atmosphere, but a nitrogen atmosphere is preferred.

[0097] In the reaction sequence, the compound represented by formulas (1) and (2) and, if necessary, the third component monomer may all be placed in a polymerization solvent at room temperature and then heated to the above temperature to polymerize, or all or part of the mixture of the compound represented by formulas (1) and (2) and, if necessary, the third component monomer may be added dropwise into a preheated polymerization solvent.

[0098] According to the latter reaction sequence, the copolymer-containing varnish of the present invention can be prepared by a manufacturing method comprising a process of dropping a mixture comprising a monomer mixture containing compounds represented by formulas (1) and (2), a polymerization solvent, and a polymerization initiator into a solvent maintained at a temperature higher than the 10-hour half-life temperature of the polymerization initiator, and reacting (polymerizing).

[0099] Above A 1The monovalent organic group having cationic properties is a cationic organic group, and examples include groups containing tertiary amines or quaternary ammonium salts. Also, the above A 1 It may be a cationic group containing an aromatic ring, and, for example, a group containing a pyridine backbone.

[0100] Above A 1 This, the following formula (2-1):

[0101] [Chemical Formula 11]

[0102]

[0103] (U b1 , U b2 and U b3 Each independently represents a hydrogen atom or a straight-chain or branched alkyl group having 1 to 5 carbon atoms, and An - It is preferable to include a structure represented by an anion selected from the group consisting of halide ions, inorganic acid ions, hydroxide ions, and isothiocyanate ions.

[0104] The above An - Preferably, halide ions, sulfate ions, phosphate ions, hydroxide ions, and isothiocyanate ions are preferred, and particularly preferred are halide ions.

[0105] Above A 1 This, the following formula (2-2):

[0106] [Chemical Formula 12]

[0107]

[0108] (R 21 ...represents an alkylene group having 1 to 6 carbon atoms that may be interrupted by a phosphate diester bond, and U b1 , U b2 and U b3 Each independently represents a hydrogen atom or a straight-chain or branched alkyl group having 1 to 5 carbon atoms, and An- It is preferable to represent an anion selected from the group consisting of halide ions, inorganic acid ions, hydroxide ions, and isothiocyanate ions.

[0109] The structure represented by the above formula (2-2) may be a betaine structure. A betaine structure refers to a monovalent or divalent group of a compound having a positive center of an acidic anionic structure and a quaternary ammonium-type cation structure, for example, a forphorylcholine group:

[0110] [Chemical Formula 13]

[0111]

[0112] Examples of compounds represented by formula (2) having such a structure include 2-methacryloyloxyethylporphorylcholine (MPC).

[0113] Method for preparing a composition for forming a coating film

[0114] The following equations (1) and (2):

[0115] [Chemical Formula 14]

[0116]

[0117] [Chemical Formula 15]

[0118]

[0119] (In Equation (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group having 1 to 6 carbon atoms, n represents an integer from 1 to 30, and in Equation (2), R 11 represents a hydrogen atom or a methyl group, and A 1A method for preparing a coating film-forming composition comprising: a process of copolymerizing a monomer mixture containing a compound represented by (which represents a monovalent organic group having cationicity) in a polymerization solvent in the presence of a radical polymerization initiator, and then a process of adding a solvent.

[0120] The present invention is a method for manufacturing in which the mass% (purity) of the compound represented by Formula (1) among the phosphorus-containing compounds included in the monomer mixture is 70 mass% or more. According to the method of the present invention, gelation of the copolymer does not occur, and a composition for forming a coating film can be manufactured in which the copolymer is stably dissolved or uniformly dispersed in a solvent.

[0121] The composition for forming a coating film according to the present invention is prepared by copolymerizing a monomer mixture containing each compound as described above, and then adding the solvent by a method known in itself.

[0122] The method for preparing a coating film-forming composition of the present invention is preferably a method for preparing a coating film-forming composition having compatibility with biomaterials.

[0123] Compatibility for biomaterials means having cell culture-promoting properties in addition to the ability to inhibit the attachment of the biomaterials described above (e.g., polymers for coating cell culture vessels described in Japanese Patent Publication No. 2014-162865, or for forming a lower membrane of cell culture described in Japanese Patent Application No. 2018-157444).

[0124] In order to form a uniform coating film, the concentration of solids in the coating film-forming composition related to the present invention is preferably 0.01 to 50 mass%. In addition, the concentration of copolymer in the coating film-forming composition is preferably 0.01 to 4 mass%, more preferably 0.01 to 3 mass%, particularly preferably 0.01 to 2 mass%, and even more preferably 0.01 to 1 mass%. If the concentration of copolymer is 0.01 mass% or less, the concentration of copolymer in the resulting coating film-forming composition is excessively low, making it impossible to form a coating film with sufficient thickness; if it is 4 mass% or more, the storage stability of the coating film-forming composition deteriorates, and there is a possibility of precipitation of dissolved substances or gelation occurring.

[0125] In order to control the ion balance of the copolymer in the composition for forming a coating film related to the present invention, when obtaining the coating film of the present invention, a process of pre-adjusting the pH of the composition for forming a coating film may be additionally included. The pH adjustment may be carried out, for example, by adding a pH adjusting agent to a composition containing the copolymer and a solvent, and adjusting the pH of the composition to 3.0 to 13.5, preferably 3.5 to 8.5, more preferably 3.5 to 7.0, or preferably 8.5 to 13.5, more preferably 10.0 to 13.5. The type and amount of the pH adjusting agent that can be used are appropriately selected according to the concentration of the copolymer or the ratio of the anion and cation present therein.

[0126] Examples of pH adjusters include organic amines such as ammonia, diethanolamine, pyridine, N-methyl-D-glucarmine, and tris(hydroxymethyl)aminomethane; alkali metal hydroxides such as potassium hydroxide and sodium hydroxide; alkali metal halides such as potassium chloride and sodium chloride; inorganic acids such as sulfuric acid, phosphoric acid, hydrochloric acid, and carbonic acid, or their alkali metal salts; quaternary ammonium cations such as choline, or mixtures thereof (e.g., buffer solutions such as phosphate-buffered physiological saline). Among these, ammonia, diethanolamine, sodium hydroxide, choline, N-methyl-D-glucarmine, and tris(hydroxymethyl)aminomethane are preferred, and ammonia, diethanolamine, sodium hydroxide, and choline are particularly preferred.

[0127] Accordingly, the present invention relates to a method for preparing a composition for forming a coating film, comprising (i) a copolymer comprising a repeating unit derived from a compound represented by Formula (1) and a repeating unit derived from a compound represented by Formula (2), (ii) a solvent, and optionally (iii) a pH adjuster. Specific examples of the copolymer, solvent, and pH adjuster are as described above.

[0128] In addition, the composition for forming a coating film according to the present invention may include other substances in addition to the copolymer and solvent, provided that such addition does not impair the performance of the resulting coating film. Examples of other substances include preservatives, surfactants, primers that enhance adhesion to the substrate, antifungal agents, and sugars.

[0129] Method for manufacturing a coating film

[0130] The method for manufacturing a coating film according to the present invention is a method for manufacturing a coating film comprising the process of applying the coating film forming composition described above to a substrate.

[0131] A composition for forming a coating film related to the present invention is applied to a gas and dried to form a coating film.

[0132] Examples of gases for forming the coating film of the present invention include glass, metal-containing compounds or metal-containing compounds, activated carbon, or resin. Examples of metal-containing compounds or metal-containing compounds include, for instance, ceramics which are sintered bodies formed by baking and hardening at high temperatures and whose basic component is a metal oxide, semiconductors such as silicon, metal oxides or metal-containing oxides (silicon oxide, alumina, etc.), metal carbides or metal-containing carbides, metal nitrides or metal-containing nitrides (silicon nitride, etc.), inorganic solid materials such as molded bodies of inorganic compounds such as metal borides or metal-containing borides, aluminum, nickel titanium, and stainless steel (SUS304, SUS316, SUS316L, etc.).

[0133] As for the resin, it may be either a natural resin or a synthetic resin; as for natural resins, cellulose, cellulose triacetic acid (CTA), cellulose with immobilized dextran sulfate, etc.; as for synthetic resins, polyacrylonitrile (PAN), polyester-based polymer alloy (PEPA), polystyrene (PS), polysulfone (PSF), polyethylene terephthalate (PET), polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), polyurethane (PU), ethylene vinyl alcohol (EVAL), polyethylene (PE), polyester (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), polyethersulfone (PES), polycarbonate (PC), polyvinyl chloride (PVC), polytetrafluoroethylene (PTFE), ultra-high molecular weight polyethylene (UHPE), polydimethylsiloxane (PDMS), acrylonitrile-butadiene-styrene resin (ABS), Teflon (registered trademark), Cycloolefin polymers (COP) (e.g., ZEONOR (registered trademark), ZEONEX (registered trademark) (manufactured by Nippon Zeon Co., Ltd.)) or various ion exchange resins are preferably used, but polystyrene (PS), polyethersulfone (PES), polypropylene (PP), and cycloolefin polymers (COP) are more preferred, and polystyrene (PS) and polyethersulfone (PES) are particularly preferred. Since the coating film of the present invention can be formed by low-temperature drying, it can be applied to resins with low heat resistance, etc.

[0134] To form the coating film of the present invention, the above-described coating film forming composition is coated on at least a portion of the surface of a gas. There are no particular limitations on the application method, and conventional application methods such as spin coating, dip coating, and solvent casting are used.

[0135] The drying process of the coating film related to the present invention is carried out under atmospheric conditions or under vacuum, preferably within a temperature range of -200°C to 200°C. Through the drying process, the solvent in the composition for forming the coating film is removed, and the phosphoric acid portion of the compound represented by Formula (1) and the cationic portion of the compound represented by Formula (2) of the copolymer related to the present invention form ionic bonds and are completely fixed to the gas.

[0136] The coating film can be formed by drying at room temperature (e.g., 10°C to 35°C, e.g., 25°C), but to form the coating film more quickly, drying may be performed at 40°C to 50°C. Alternatively, a drying process at extremely low to low temperatures (e.g., -200°C to -30°C) using the freeze-drying method may be used. Freeze-drying is also called vacuum freeze-drying, and it is a method in which the object to be dried is cooled with a refrigerant and the solvent is removed by sublimation in a vacuum. Common refrigerants used in freeze-drying include a mixture of dry ice and methanol (-78°C) and liquid nitrogen (-196°C).

[0137] If the drying temperature is -200 ℃ or lower, it lacks versatility because an uncommon refrigerant must be used, and it is inefficient because drying requires a long time for solvent sublimation. If the drying temperature is 200 ℃ or higher, the ionic bonding reaction on the surface of the coating film proceeds excessively, causing the surface to lose hydrophilicity, and thus the ability to inhibit the attachment of biomaterials is not exhibited. More desirable drying temperatures are 10 ℃ to 190 ℃, 10 ℃ to 180 ℃, 10 ℃ to 170 ℃, 10 ℃ to 160 ℃, 20 ℃ to 180 ℃, 20 ℃ to 170 ℃, 20 ℃ to 160 ℃, 20 ℃ to 150 ℃, and 25 ℃ to 150 ℃.

[0138] After drying, a cleaning process may be performed using at least one solvent selected from an aqueous solution containing water and an electrolyte to remove impurities, unreacted monomers, etc. remaining on the coating film, and furthermore to control the ion balance of the copolymer in the film. Cleaning is preferably performed using flowing water or ultrasonic cleaning. The aqueous solution containing water and an electrolyte may be heated, for example, in the range of 40°C to 95°C. The aqueous solution containing the electrolyte is preferably PBS, physiological saline (containing only sodium chloride), Dulbecco phosphate-buffered physiological saline, Tris-buffered physiological saline, HEPES-buffered physiological saline, and Veronal-buffered physiological saline, and PBS is particularly preferred. After fixation, the coating film does not leach out even when cleaned with water, PBS, alcohol, etc., and remains firmly fixed to the gas. Even if biological material adheres to the formed coating film, it can be easily removed by washing with water, etc., and thus the gas surface on which the coating film of the present invention is formed has the ability to inhibit the attachment of biological material.

[0139] As an example of an application of the coating film of the present invention, a coating film for a filter of an artificial dialysis machine is used, but the coating film of the present invention has good adhesion to synthetic resins (e.g., PES, PS, and PSF, etc.) used in filters, and good durability after adhesion. The form of the film is not particularly limited and may be a substrate, fiber, particle, gel, porous form, etc., and the shape may be a flat plate or a curved surface.

[0140] For example, when used as a coating film for a filter of an artificial dialysis machine, the coating film forming composition related to the present invention can be passed through the inner side of a filter having a hollow fiber shape with a diameter of, for example, 0.1 to 500 μm made of the above material, and then manufactured through a drying process and a washing process (washing with hot water (e.g., 40°C to 95°C), etc.).

[0141] Depending on the needs, treatments such as γ rays, ethylene oxide, and autoclaves may be used for sterilization.

[0142] The film thickness of the coating film of the present invention is preferably 10 to 1000 Å, more preferably 10 to 500 Å, and most preferably 20 to 400 Å.

[0143] The coating film of the present invention has the ability to inhibit the adhesion of biomaterials, so it can be preferably used as a coating film for medical substrates. For example, it can be preferably used in leukocyte removal filters, blood transfusion filters, virus removal filters, microclot removal filters, blood purification modules, artificial hearts, artificial lungs, blood circuits, artificial blood vessels, vascular bypass tubes, medical tubes, artificial valves, cannulas, stents, catheters, intravascular catheters, balloon catheters, guide wires, sutures, retaining needles, shunts, artificial joints, artificial hip joints, blood bags, blood preservation containers, surgical aids, adhesion barriers, wound dressings, etc. Here, a blood purification module refers to a module that has the function of removing waste products or harmful substances from the blood by circulating blood outside the body, and examples include artificial kidneys, toxin adsorption filters or columns.

[0144] In addition, the coating film of the present invention is useful as a coating film for cell culture vessels such as flasks, dishes, and plates, or for various research instruments that inhibit protein adhesion.

[0145] In addition, the coating film-forming composition of the present invention is also useful as a cosmetic material, a contact lens care product material, a skin care textile processing agent, a diagnostic medicinal material for biochemical research, a blocking agent for inhibiting non-specific adsorption in enzyme immunoassay (ELISA) or latex agglutination methods widely used in clinical diagnostic methods, and a stabilizer for stabilizing proteins such as enzymes or antibodies.

[0146] In addition, the coating film of the present invention is also useful as a coating film for toiletries, personal care products, detergents, pharmaceuticals, quasi-pharmaceuticals, textiles, and antifouling materials.

[0147] Examples

[0148] The present invention will be described in more detail below with reference to examples, etc., but the present invention is not limited in any way by the following examples, etc.

[0149] Method for Measuring Monomer Purity

[0150] The mass % (purity) of the acid phosphooxypolypropylene glycol monomethacrylate (average added moles of propylene oxide 5) (product name; PPM-5P, manufactured by Toho Chemical Co., Ltd.) used in the following synthesis example is: 31 After analyzing the composition of phosphorus-containing compounds using P-NMR measurement, the molecular weight was obtained by conversion using the added moles of acid phosphooxypolypropylene glycol monomethacrylate (average added moles of propylene oxide 5) as 5.

[0151] ( 31 P-NMR measurement conditions)

[0152] · Device: AVANCE III HD (500 MHz)

[0153] · Solvent: Biacetone

[0154] · Measured temperature: Room temperature (23 ℃)

[0155] · Measurement conditions: Non-decoupling method

[0156] · Measurement data points: 131,072 (128 k)

[0157] · Pulse width: 90° pulse (14 μsec.)

[0158] · Measurement range: -50 to 10 ppm

[0159] · Total count: 256 times

[0160] Method for Measuring the Molecular Weight of Copolymers

[0161] The weight average molecular weight of the copolymer shown in the following synthesis example is the result of measurement by Gel Filtration Chromatography (hereinafter abbreviated as GFC).

[0162] (Measurement conditions)

[0163] · Device: HLC-8320GPC (Manufactured by Tosoh Corp.)

[0164] ·GFC Column: TSKgel GMPWXL (7.8 mm ID × 30 cm) × 2 to 3 pieces

[0165] · Eluent: Aqueous solution containing ionic substances, or a mixed solution of EtOH (ethanol)

[0166] · Column temperature: 40 ℃

[0167] · Detector: RI

[0168] · Injection concentration: Polymer solids 0.05 ~ 0.5 %

[0169] · Infusion volume: 100 µl

[0170] · Calibration curve: cubic approximation curve

[0171] · Standard Sample: Polyethylene Oxide (Manufactured by Agilent) × 10 types

[0172] <Synthesized Example 1>

[0173] 16.70 g of ethanol was added to 2.27 g of acid phosphooxypolypropylene glycol monomethacrylate (average added moles of propylene oxide 5) (product name; PPM-5P, manufactured by Toho Chemical Co., Ltd., mass% (purity) 95.6 mass%) and dissolved sufficiently. Then, 0.80 g of 2-(dimethylamino)ethyl methacrylate (manufactured by Tokyo Kasei Kogyo Co., Ltd.) and 11.23 g of pure water were added and stirred well, and then 15.7 mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name; VE-073, manufactured by Fujifilm Wako Junyaku Co., Ltd.) was added. A 100 ml flask containing the above-mentioned homogenized mixed solution, which had been sufficiently stirred, was nitrogen-submerged and heated to the reflux temperature while stirring (oil bath temperature set to 95°C). By heating and stirring while maintaining the above environment for 24 hours, a copolymer-containing varnish with a solid content of approximately 10.60 mass% was obtained. The weight average molecular weight of the obtained transparent liquid GFC was approximately 310,000.

[0174] <Synthesized Example 2>

[0175] 0.89 g of 2-methacryloyloxyethylporphorylcholine (MPC, manufactured by Tokyo Kasei Kogyo Co., Ltd.) and 1.37 g of acid phosphooxypolypropylene glycol monomethacrylate (average added moles of propylene oxide 5) (product name; PPM-5P, manufactured by Toho Chemical Co., Ltd., mass% (purity) 95.6 mass%) were added to a mixed solvent of 10.46 g of pure water and 10.14 g of ethanol, and stirred well. Then, 6 mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name; VE-073, manufactured by Fujifilm Wako Junyaku Co., Ltd.) was added, and stirred sufficiently until homogeneous. A copolymer-containing varnish with a solid content of approximately 9.93 mass% was obtained by purging nitrogen into a 100 ml flask containing this mixed solution, raising the temperature to 70°C, and heating and stirring for 7 hours. The weight average molecular weight of the obtained transparent liquid in GFC was approximately 750,000.

[0176] <Synthesized Example 3>

[0177] 1.25 g of 2-methacryloyloxyethylporphorylcholine (MPC, manufactured by Tokyo Kasei Kogyo Co., Ltd.) and 0.84 g of acid phosphooxypolypropylene glycol monomethacrylate (average added moles of propylene oxide 5) (product name; PPM-5P, manufactured by Toho Chemical Co., Ltd., mass% (purity) 95.6 mass%) were added to a mixed solvent of 8.51 g of pure water and 8.59 g of ethanol, and the mixture was stirred well. Then, 6 mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name; VE-073, manufactured by Fujifilm Wako Junyaku Co., Ltd.) was added, and the mixture was stirred sufficiently until homogeneous. A copolymer-containing varnish with a solid content of approximately 11.20 mass% was obtained by purging nitrogen into a 100 ml flask containing this mixed solution, raising the temperature to 70°C, and heating and stirring for 7 hours. The weight average molecular weight of the obtained transparent liquid in GFC was approximately 710,000.

[0178] <Synthesized Example 4>

[0179] 1.62 g of 2-methacryloyloxyethylporphorylcholine (MPC, manufactured by Tokyo Kasei Kogyo Co., Ltd.) and 0.28 g of acid phosphooxypolypropylene glycol monomethacrylate (average added moles of propylene oxide 5) (product name; PPM-5P, manufactured by Toho Chemical Co., Ltd., mass% (purity) 95.6 mass%) were added to a mixed solvent of 8.60 g of pure water and 8.52 g of ethanol, and stirred well. Then, 6 mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name; VE-073, manufactured by Fujifilm Wako Junyaku Co., Ltd.) was added, and stirred sufficiently until homogeneous. A copolymer-containing varnish with a solid content of approximately 10.36 mass% was obtained by purging nitrogen into a 100 ml flask containing this mixed solution, raising the temperature to 70°C, and heating and stirring for 7 hours. The weight average molecular weight of the obtained transparent liquid in GFC was approximately 390,000.

[0180] <Synthesized Examples 5–12>

[0181] Based on Synthesis Example 1, a polymer was obtained using a monomer composition with the monomers and composition ratios shown in the table. The results of analyzing the molecular weight of the obtained polymer in the same manner as in Synthesis Example 1 are shown in Table 1.

[0182] In addition, in Table 1, PEM5P represents acid phosphooxyethylene glycol monomethacrylate (average added moles of ethylene oxide 5) (Product name; PEM-5P, manufactured by Toho Chemical Co., Ltd., mass% (purity) 87.4 mass%), MHP represents acid phosphooxyhexyl monomethacrylate (Product name; MHP, manufactured by Toho Chemical Co., Ltd., mass% (purity) 94.2 mass%), DMMA represents 2-(dimethylamino)ethyl methacrylate (manufactured by Tokyo Kasei Kogyo Co., Ltd.), DEMA represents 2-(diethylamino)ethyl methacrylate (manufactured by Tokyo Kasei Kogyo Co., Ltd.), and MACC represents an approximately 80% aqueous solution of methacloylcholine chloride (manufactured by Tokyo Kasei Kogyo Co., Ltd.).

[0183] In addition, the mass % (purity) of PEM5P and MHP was analyzed for composition using the same method as that used for PPM5P described in Synthesis Examples 1 to 4. For PEM5P, the mass % was determined by conversion using the molecular weight when the number of moles of added ethylene oxide was 5.

[0184]

[0185] <Comparative Synthesis Example 1>

[0186] The mass % of the phosphorus-containing compound of acid phosphooxyethyl methacrylate described below is as described in republished Patent No. 2016 / 093293 31 This is a value obtained by P-NMR measurement.

[0187] 9.22 g of ethanol was added to 1.06 g of acid phosphooxyethyl methacrylate (product name; Posmer M, manufactured by Uni Chemical Co., Ltd., non-volatile content at 100 ℃ for 1 hour in the drying method: 91.8%, mass% of each component: mixture of acid phosphooxyethyl methacrylate (44.2 mass%), bis[2-(methacryloyloxy)ethyl] phosphate (28.6 mass%), and other substances (27.2 mass%)) and dissolved sufficiently. Next, 0.72 g of 2-(dimethylamino)ethyl methacrylate (manufactured by Tokyo Kasei Kogyo Co., Ltd.) and 6.00 g of pure water were added and stirred thoroughly, after which 8.6 mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Junyaku Co., Ltd.) was added. After sufficient stirring to homogenize the mixture, the 50 ml flask containing the above ingredients was subjected to nitrogen purging, and the temperature was raised to the reflux temperature while stirring (oil bath temperature set to 95 ℃). This state was maintained and heated and stirred, but a white precipitate formed within 1 hour.

[0188] <Comparative Synthesis Example 2>

[0189] 0.90 g of 2-methacryloyloxyethylphorphorylcholine (MPC, manufactured by Tokyo Kasei Kogyo Co., Ltd.) and 0.73 g of acid phosphooxyethyl methacrylate (product name; Posmer M, manufactured by Uni Chemical Co., Ltd., non-volatile content at 100°C for 1 hour in the drying method: 91.8%, mass% of each component: mixture of acid phosphooxyethyl methacrylate (44.2 mass%), bis[2-(methacryloyloxy)ethyl] phosphate (28.6 mass%), and other substances (27.2 mass%)) were added to a mixed solvent of 7.26 g of pure water and 7.24 g of ethanol, and stirred well. Next, 6 mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Junyak Co., Ltd.) was added and stirred sufficiently until homogeneous. Nitrogen was applied to the 50 mL flask containing this mixed solution, and after raising the temperature to 70 °C and maintaining this state, heating and stirring were performed; however, a white precipitate formed within 3 hours.

[0190] <Example 1>

[0191] To 0.80 g of the copolymer-containing varnish obtained in Synthesis Example 1 above, 5.05 g of pure water, 1.94 g of ethanol, and 0.20 g of 0.1 mol / ℓ hydrochloric acid (used by diluting 1 N hydrochloric acid (manufactured by Kanto Chemical Co., Ltd.) 10 times with pure water) were added and thoroughly stirred to prepare a composition for forming a coating film. The pH was 4.6. The obtained composition for forming a coating film was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and as a drying process, it was dried in an oven at 50°C for 24 hours. Afterward, the mixture was thoroughly washed with a phosphate buffer (hereinafter abbreviated as PBS) and dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The thickness of the coating film on the silicon wafer after HMDS treatment was determined using a spectroscopic ellipsometer and was 3.9 nm.

[0192] <Example 2>

[0193] 0.80 g of the copolymer-containing varnish obtained in Synthesis Example 1 above was mixed with 5.26 g of pure water and 1.94 g of ethanol and stirred thoroughly to prepare a composition for forming a coating film.

[0194] The pH was 5.9. The obtained coating film forming composition was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Afterward, the wafer was thoroughly washed with phosphate buffer (hereinafter abbreviated as PBS) and then dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The film thickness of the coating film on the silicon wafer that had undergone HMDS treatment was confirmed using a spectroscopic ellipsometer, and it was 4.0 nm.

[0195] <Example 3>

[0196] To 0.80 g of the copolymer-containing varnish obtained in Synthesis Example 1 above, 4.84 g of pure water and 1.95 g of ethanol were added and stirred thoroughly, and 0.26 g of a 0.1 mol / ℓ aqueous sodium hydroxide solution (using 1 N sodium hydroxide (manufactured by Kanto Chemical Co., Ltd.) diluted 10 times with pure water) was added and stirred thoroughly to prepare a composition for forming a coating film. The pH was 7.0. The obtained composition for forming a coating film was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Afterward, the mixture was thoroughly washed with a phosphate buffer (hereinafter abbreviated as PBS) and dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The thickness of the coating film on the silicon wafer after HMDS treatment was determined using a spectroscopic ellipsometer and was 3.9 nm.

[0197] <Example 4>

[0198] To 2.00 g of the copolymer-containing varnish obtained in Synthesis Example 2 above, 9.00 g of pure water and 9.00 g of ethanol were added and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.8. The obtained composition for forming a coating film was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Afterward, the coating was thoroughly washed with PBS and dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The film thickness of the coating film on the silicon wafer that had undergone HMDS treatment was confirmed using a spectroscopic ellipsometer, and it was 3.9 nm.

[0199] <Example 5>

[0200] To 2.00 g of the copolymer-containing varnish obtained in Synthesis Example 3 above, 9.00 g of pure water and 9.00 g of ethanol were added and thoroughly stirred to prepare a composition for forming a coating film.

[0201] The pH was 3.1. The obtained coating film-forming composition was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Afterward, the wafer was thoroughly washed with PBS and dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The film thickness of the coating film on the silicon wafer that had undergone HMDS treatment was confirmed using a spectroscopic ellipsometer, and it was 3.5 nm.

[0202] <Example 6>

[0203] To 2.00 g of the copolymer-containing varnish obtained in Synthesis Example 4 above, 9.00 g of pure water and 9.00 g of ethanol were added and thoroughly stirred to prepare a composition for forming a coating film. The pH was 3.3. The obtained composition for forming a coating film was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Afterward, the coating was thoroughly washed with PBS and dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The film thickness of the coating film on the silicon wafer that had undergone HMDS treatment was confirmed using a spectroscopic ellipsometer, and it was 3.1 nm.

[0204] <Example 7>

[0205] To 1.00 g of the copolymer-containing varnish obtained in Synthesis Example 5 above, 2.60 g of pure water and 6.40 g of ethanol were added and thoroughly stirred to prepare a composition for forming a coating film. The pH was 3.6. The obtained composition for forming a coating film was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Afterward, the coating was thoroughly washed with PBS and dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The film thickness of the coating film on the silicon wafer that had undergone HMDS treatment was confirmed using a spectroscopic ellipsometer, and it was 3.5 nm.

[0206] <Example 8>

[0207] To 1.00 g of the copolymer-containing varnish obtained in Synthesis Example 8 above, 2.60 g of pure water and 6.40 g of ethanol were added and thoroughly stirred to prepare a composition for forming a coating film. The pH was 6.8. The obtained composition for forming a coating film was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Afterward, the coating was thoroughly washed with PBS and dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The film thickness of the coating film on the silicon wafer that had undergone HMDS treatment was confirmed using a spectroscopic ellipsometer, and it was 3.8 nm.

[0208] <Example 9>

[0209] To 1.00 g of the copolymer-containing varnish obtained in Synthesis Example 10 above, 2.50 g of pure water and 6.40 g of ethanol were added and stirred thoroughly, and 0.11 g of a 0.1 mol / ℓ aqueous sodium hydroxide solution (using 1 N sodium hydroxide (manufactured by Kanto Chemical Co., Ltd.) diluted 10 times with pure water) was added and stirred thoroughly to prepare a composition for forming a coating film. The pH was 4.2. The obtained composition for forming a coating film was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and as a drying process, dried in an oven at 50°C for 24 hours. Afterward, the wafer was thoroughly washed with PBS and dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The thickness of the coating film on the silicon wafer after HMDS treatment was determined using a spectroscopic ellipsometer and was 3.7 nm.

[0210] <Reference Example 1>

[0211] A composition for forming a coating film was prepared by adding 49.75 g of ethanol to 0.25 g of Lipidure-CM5206 (manufactured by Nichiyu Co., Ltd.) and stirring thoroughly. The obtained composition for forming a coating film was spin-coated onto a silicon wafer that had undergone HMDS treatment at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Subsequently, the wafer was thoroughly washed with PBS and dried in an oven at 50°C for 1 hour to obtain a coating film on the silicon wafer that had undergone HMDS treatment. The film thickness of the coating film on the silicon wafer that had undergone HMDS treatment was confirmed using a spectroscopic ellipsometer, and it was 25.4 nm.

[0212] <Test Example 1: Cell Adhesion Inhibitory Effect>

[0213] (Preparation of coating plates)

[0214] The coating film-forming composition prepared in Examples 1 to 3, 8, and 9 was added to different wells of a 96-hole cell culture plate (Corning, #351172, volume 0.37 ml, made of polystyrene) at a rate of 200 µl / well, and after standing at room temperature for 1 hour, the excess varnish was removed. The plates were dried in an oven at 50°C for 24 hours. Afterward, each coated well was washed three times with 250 µl of pure water, dried in an oven at 50°C for 1 hour, and then used for testing. As a positive control, the coating film-forming composition prepared in Reference Example 1 was used, coated onto the wells of a 96-hole cell culture plate (Corning, #351172, volume 0.37 ml, made of polystyrene) using the same method as above. As a negative control, an uncoated 96-hole cell culture plate (manufactured by Corning, #351172, volume 0.37 ml, made of polystyrene) was used.

[0215] (Preparation of cells)

[0216] Mouse embryonic filamentous blast cells (manufactured by DS Pharma Biomedical) were used. The culture medium used for the cells was BME medium (manufactured by Thermo Fisher Scientific) containing 10% FBS (manufactured by Sigma-Aldrich) and L-glutamine-penicillin-streptomycin stabilizing solution (manufactured by Thermo Fisher Scientific). The cells were statically cultured for at least 2 days in a 10 cm diameter petri dish (10 mL of medium) in a 37 ℃ / CO2 incubator while maintaining a 5% carbon dioxide concentration. Next, the cells were washed with 5 ml of PBS, 1 ml of 0.25 w / v% trypsin-1 ml / ℓ EDTA solution (manufactured by Fujifilm Wako Pure Medicine Co., Ltd.) was added to remove the cells, and each was suspended in 10 ml of the above medium. After centrifuging the suspension (manufactured by Tomi Seikou Co., Ltd., model number LC-200, 1000 rpm / 3 min, room temperature), the supernatant was removed, and the above medium was added to prepare a cell suspension.

[0217] (Cell adhesion experiment)

[0218] For each well of the plate prepared above, the positive control, and the negative control, each cell suspension is 1 × 10⁶ 4 150 µl was added to each well to achieve a cell / well ratio. Afterward, the cells were incubated in a CO2 incubator at 37°C for 3 days while maintaining a 5% carbon dioxide concentration.

[0219] (Observation of cell adhesion)

[0220] After 3 days of culture, cell attachment to each well of the plate prepared above, the positive control, and the negative control was compared based on observation using an inverted microscope (Olympus CKX31, magnification: 4x). In the wells of the plates coated with the coating agent of Examples 1 to 3, 8, 9 and the positive control (Reference Example 1), no cell attachment was observed, while cell attachment was observed in the wells of the negative control. The results for Examples 1 to 3, the positive control, and the negative control are shown in Figures 1 to 5, respectively.

[0221] <Test Example 2: Protein Adsorption Inhibitory Effect>

[0222] (Manufacturing of QCM Sensor (PS))

[0223] An Au-deposited quartz oscillator (Q-Sense, QSX301) was cleaned at 50 mA / 3 min using a soft etching device (manufactured by Maywa Forces Co., Ltd., SEDE-GE), and immediately thereafter, it was immersed for 24 hours in a solution of 0.0772 g of 2-amine ethanethiol (manufactured by Tokyo Kasei Kogyo Co., Ltd.) dissolved in 1000 ml of ethanol. After cleaning the sensor surface with ethanol and air-drying it, a varnish of 1.00 g of polystyrene (PS) (manufactured by Sigma-Aldrich) dissolved in 99.00 g of toluene was spin-coated onto the film sensor side using a spin coater at 3500 rpm / 30 sec, and dried at 150 ℃ / 1 min to make a QCM sensor (PS).

[0224] (Manufacturing of QCM sensors (SiO2))

[0225] A SiO2-deposited quartz oscillator (Q-Sense, QSX303) was cleaned using a soft etching device (manufactured by Maywa Forces Co., Ltd., SEDE-GE) at 50 mA / 3 min and used as is.

[0226] (Preparation of surface-treated QCM sensors (PS) and surface-treated QCM sensors (SiO2))

[0227] The coating film-forming composition obtained in Examples 1 to 4, 7 to 9 and Reference Example 1 was spin-coated onto a QCM sensor (PS) at 3500 rpm / 30 sec, and as a drying process, it was fired in an oven at 50°C for 24 hours. Afterwards, as a cleaning process, the excess coating film-forming composition was washed twice each with PBS and pure water, and surface-treated QCM sensors (PS) (substrates No. 1 to 5, 11 to 13) were obtained. Likewise, the coating film-forming composition obtained in Examples 4 to 6 was spin-coated onto a QCM sensor (SiO2) at 3500 rpm / 30 sec, and as a drying process, it was fired in an oven at 50°C for 24 hours. Afterwards, as a cleaning process, the excess coating film forming composition was washed twice each with PBS and pure water to obtain surface-treated QCM sensors (SiO2) (substrates No. 7 to 9). As a positive control, a surface-treated QCM sensor (PS) (substrate No. 5) coated with the coating film forming composition obtained in Reference Example 1 was used. As negative controls, a QCM sensor (PS) (substrate No. 6) and a QCM sensor (SiO2) (substrate No. 10) were used.

[0228] (Protein adsorption experiment)

[0229] Surface-treated QCM sensors (PS) (substrates No. 1–5, 11–13) and surface-treated QCM sensors (SiO2) (substrates No. 7–9), manufactured by the above method using a composition for forming a coating film, were mounted on a dissipative quartz crystal oscillator microbalance QCM-D (E4, Q-Sense), and PBS was flowed until a stable baseline was established in which the frequency change was 1 Hz or less per hour. Next, the frequency of the stable baseline was set to 0 Hz, and PBS was flowed for about 10 minutes. Subsequently, a 100 μg / ml PBS solution of human serum-derived γ-globulin was flowed for about 30 minutes, and then PBS was flowed again for about 20 minutes, after which the shift (Δf) of the adsorption-induced frequency of the 9th overtone was read. Q-Tools (Q-Sense) was used for analysis, and the shift (Δf) of the adsorption-inducing frequency described by the Sauerbrey equation, converted into mass per unit area (ng / cm²), is shown in Table 2 below as the amount of biomaterial attached. Substrates No. 1 to 4, No. 7 to 9, and No. 11 to 13, which used the coating film-forming composition of Examples 1 to 9 related to the present invention as a coating, showed a lower amount of protein adsorption compared to substrates No. 6 and 10 without coating.

[0230]

[0231] Industrial applicability

[0232] According to the present invention, a method for manufacturing a copolymer-containing varnish that does not cause gelation problems, a method for manufacturing a composition, a method for manufacturing a coating film, and preferably a method for manufacturing a coating film having compatibility with biomaterials (having the ability to inhibit biomaterial adhesion or promote cell culture) can be provided.

[0233] The coating film of the present invention has the ability to inhibit the adhesion of biomaterials, so it can be preferably used as a coating film for medical substrates. For example, it can be preferably used in leukocyte removal filters, blood transfusion filters, virus removal filters, microclot removal filters, blood purification modules, artificial hearts, artificial lungs, blood circuits, artificial blood vessels, vascular bypass tubes, medical tubes, artificial valves, cannulas, stents, catheters, intravascular catheters, balloon catheters, guide wires, sutures, retaining needles, shunts, artificial joints, artificial hip joints, blood bags, blood preservation containers, surgical aids, adhesion barriers, wound dressings, etc. Here, a blood purification module refers to a module that has the function of removing waste products or harmful substances from the blood by circulating blood outside the body, and examples include artificial kidneys, toxin adsorption filters or columns.

[0234] In addition, the coating film of the present invention is useful as a coating film for cell culture vessels such as flasks, dishes, and plates, or for various research instruments that inhibit protein adhesion.

[0235] In addition, the coating film of the present invention is also useful as a cosmetic material, a contact lens care product material, a skin care textile processing agent, a diagnostic medicinal material for biochemical research, a blocking agent for inhibiting non-specific adsorption in enzyme immunoassay (ELISA) or latex agglutination methods widely used in clinical diagnostics, and a stabilizer for stabilizing proteins such as enzymes or antibodies.

[0236] In addition, the coating film of the present invention is also useful as a coating film for toiletries, personal care products, detergents, pharmaceuticals, quasi-pharmaceuticals, textiles, and antifouling materials.

Claims

Claim 1 The following equations (1) and (2): (In Equation (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group having 1 to 6 carbon atoms, n represents an integer from 1 to 30, and in Equation (2), R 11 represents a hydrogen atom or a methyl group, and A 1 A method for manufacturing a copolymer-containing varnish comprising a process of copolymerizing a monomer mixture containing a compound represented by (a monovalent organic group having cationic properties) in a polymerization solvent in the presence of a radical polymerization initiator, wherein the mass% of the compound represented by Formula (1) among the phosphorus-containing compounds contained in the monomer mixture is 85 mass% or more. Claim 2 In claim 1, the above A 1 This, the following formula (2-1): (U b1 , U b2 and U b3 Each independently represents a hydrogen atom or a straight-chain or branched alkyl group having 1 to 5 carbon atoms, and An - A method for manufacturing a copolymer-containing varnish comprising a structure represented by (which represents an anion selected from the group consisting of halide ions, inorganic acid ions, hydroxide ions, and isothiocyanate ions). Claim 3 In claim 1, the above A 1 This, the following formula (2-2): (R 21 ...represents an alkylene group having 1 to 6 carbon atoms that may be interrupted by a phosphate diester bond, and U b1 , U b2 and U b3 Each independently represents a hydrogen atom or a straight-chain or branched alkyl group having 1 to 5 carbon atoms, and An - A method for manufacturing a copolymer-containing varnish, represented by an anion selected from the group consisting of halide ions, inorganic acid ions, hydroxide ions, and isothiocyanate ions. Claim 4 The following equations (1) and (2): (In Equation (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group having 1 to 6 carbon atoms, n represents an integer from 1 to 30, and in Equation (2), R 11 represents a hydrogen atom or a methyl group, and A 1 A method for preparing a coating film-forming composition comprising a process of copolymerizing a monomer mixture containing a compound represented by (a monovalent organic group having cationicity) in a polymerization solvent in the presence of a radical polymerization initiator, followed by a process of adding a solvent, wherein the mass% of the compound represented by Formula (1) among the phosphorus-containing compounds contained in the monomer mixture is 85 mass% or more. Claim 5 In claim 4, a method for preparing a composition for forming a coating film having compatibility with biomaterials. Claim 6 A method for manufacturing a coating film, comprising the process of applying a coating film-forming composition described in claim 4 or 5 to a substrate.

Citation Information

Patent Citations

  • Polymeric surface coatings

    EP0593561A1

  • Polymer useful for making surface organism and blood-compatible

    JP1999166015A

  • Ion complex material having function of inhibiting adhesion of biological matter and production method for same

    KR1020160015309A

  • Growth of cells

    US20140186945A1

  • Polymeric surface coatings

    WO1993001221A1